The place of precedent and legislation as sources of law in legal doctrine - حسن وکیلیان (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2018)
This paper explains the status of jurisprudence and legislation as the main sources of law in common law and written law traditions. It is argued that lawyers’ attitude toward aforementioned sources within both traditions has changed during recent decades. Indeed, plurality of the legal sources has been recognized gradually due to relative advantages of both sources. It is maintained that judicial lawmaking can be deemed as complementary source of law alongside legislation. In practice, based on this premises, it is explained that in some jurisdictions, lawyers and legal scholars within written law tradition have recognized more important role of jurisprudence in their lawmaking process. Traditional views towards the role of the judges as mere interpreters of Statutes have changed and their constructive role in developing the legal system as lawmakers has been recognized. It is claimed that decentralized lawmaking (or law finding) system is more appropriate for liberty and market oriented economy. It is believed that judge made law is more efficient than legislation. In contrast, supporters of legislation emphasis on some values such as certainty, clarity and predictability of law making through legislation. Finally, it is suggested that status of jurisprudence within domestic legal system shall be reviewed by Iranian lawyers.